Teacher’s Perception on Applying Lapbook as a Learning Media in Writing Descriptive Text through Cooperative Learning Method - Binti, Titania (Lembaga Bale Literasi, 2025)
The research aims to explore the teaching and learning process of descriptive text using lapbook media through cooperative learning method and teachers' perceptions regarding the application of this method and media. This research needs to be carried out because in SMAN 3 teacher who used lapbook media and cooperative learning method was successful in teaching descriptive text, so the researchers explored the learning process to increase insight for other teachers. This research used case study design with qualitative data from the results of semi-structured interviews conducted with one teacher who implemented cooperative learning method with lapbooks in teaching descriptive writing at SMANN 3 Pamekasan. This research found that the teaching and learning process of descriptive writing consisted of opening section and giving stimulation about descriptive text, then continue to dividing the class in to six groups to make a lapbook and giving a theme to each group. Each group will make and finish their lapbook. The teacher asked each group to present their lapbook and other group will give feedback. This study also found the teacher’s perception of the using lapbook media and cooperative learning method in teaching descriptive writing. The perceptions are students enjoyed the learning process, learnt to think critically and tried to solve their own problems in learning, could work together and help each other, showed their creativity, easier to manage the class. But the teacher also found difficulties in teaching descriptive writing using lapbook media with cooperative learning method such as lack of time.